PENINGKATAN KUALITAS HIDUP SISWA SMKN 1 LELEA KABUPATEN INDRAMAYU DALAM MENGATASI STRES PERKEMBANGAN MASA REMAJA - Suryadi, Denrich; Chandra, Julyarno; Audrey, Mikaella; Alodia, Natasya; Mulapoa, Cyindy; Dwininta, Andini (Jurnal Bakti Masyarakat Indonesia, 2022)
SMKN 1 Lelea, which is located in area of Nagrak, Taman Sari Village, consists of 1,461 students who live in the Lelea sub-district, Indramayu district. Counseling teacher team that handles the students of SMKN 1 needs help to provide education about dealing with adolescent stress related to academic problems, personal/family problems and adolescent problems in general. The purpose of this PKM program is to provide psychoeducation about the stress of adolescent development and how to deal with stress ef ectively. The current target of PKM is for students of SMKN 1 Lelea class X, amounting to 461 people. The Project MBKM group in the Village that helps SMKN 1 Lelea conducted a survey on February 23, 2022 and designed two activities, namely psychoeducational activities on how students are able to cope with various stresses faced during adolescent development on March 21, 2022 and counseling activities. peer group for class X students of SMKN 1 Lelea who need personal counseling which will take place on March 24-30, 2022. The result of this activity is an increase in knowledge about stress, its impact and practical ways of dealing with stress on adolescent development in students of SMKN 1 Lelea class X who are attended by 130 participants. While peer counseling activities were also attended by 17 students with feedback in the form of feeling calmer. relieved, happy, more motivated, less stressed, more able to introspect, open to problems and feelings, increase knowledge, and get more support from the counseling process. ABSTRAK: SMKN 1 Lelea yang terletak di dusun Nagrak, Desa Taman Sari memiliki 1.461 siswa yang berdomisili di kecamatan Lelea kabupaten Indramayu. Tim guru BK SMKN 1 Lelea membutuhkan bantuan untuk memberikan edukasi mengenai penanganan stres remaja terkait dengan masalah akademik, masalah pribadi/keluarga dan masalah remaja pada umumnya. Tujuan program PKM ini untuk memberikan psikoedukasi mengenai stres perkembangan masa remaja dan cara efektif mengatasi stres. Sasaran PKM saat ini pada siswa SMKN 1 Lelea kelas X yang berjumlah 461 orang. Kelompok MBKM Proyek di Desa yang membantu SMKN 1 Lelea telah melakukan survei pada tanggal 23 Februari 2022 dan merancang dua buah kegiatan yaitu kegiatan psikoedukasi mengenai bagaimana cara siswa/i mampu mengatasi berbagai stres yang dihadapi dalam masa perkembangan remaja pada tanggal 21 Maret 2022 dan kegiatan konseling sebaya bagi siswa kelas X SMKN 1 Lelea yang membutuhkan konseling secara pribadi yang berlangsung pada tanggal 24-30 Maret 2022. Hasil kegiatan ini adalah bertambahnya pengetahuan mengenai stres, dampak dan cara praktis mengatasi stres perkembangan remaja pada siswa/i SMKN 1 Lelea kelas X yang diikuti oleh 130 orang peserta. Hasil pre-test dan post-test untuk menunjukkan perbedaan pengaruh informasi dalam seminar terlihat perubahan yang signifikan. Sedangkan kegiatan konseling sebaya juga diikuti oleh 17 orang siswa dengan umpan balik berupa perasaan lebih tenang. lega, senang, lebih termotivasi, tidak tertekan, lebih mampu introspeksi diri, terbuka dengan masalah dan perasaan, menambah pengetahuan, dan mendapatkan lebih banyak dukungan dari proses konseling tersebut.